Kajian Proporsi Wajah Wayang Potehi Perempuan di Gudo, Jombang dengan Proporsi Rasio Emas - Mangunsong, Hasprita Restiamangastuti Boru; Djatiprambudi, Djuli (Gelar: Jurnal Seni Budaya, 2021)
The interaction of Nusantara with various  nations that has occurred since long ago led to the acculturation of local and immigrant cultures and produced a new culture. One of them is Wayang Potehi which comes from China and develops in Java. The purpose of this study is to find and describe the facial proportions of the female character of Wayang Potehi in Gudo, Jombang. The method used is a quantitative research method by measuring the facial proportions of several female characters of Wayang Potehi in Gudo with the golden ratio theory and calculating the average. In addition, this research also applies interviews with the chairman, Toni, and the puppeteer of Hok Ho An (Wayang Potehi Gudo group), Sonny, as well as direct observation. The golden ratio theory is not used to assess the proportion of Wayang Potehi but as a tool to find the average size of the proportion. The result of this study is the acculturation of Chinese and Javanese culture in visuals, language, stories, characters and characteristics as well as the artists behind the Potehi Wayang. The majority of Wayang Potehi are recognized by the symbols on their clothes and accessories, especially for female characters. Some of the female characters of Wayang Potehi created by the sculptor and Toni's team are quite different from the female characters of Wayang Potehi from China. This shows that the background of the artist (Javanese) influences the work of Wayang Potehi production.